ISOPIESTIC MEASUREMENT OF THE OSMOTIC AND ACTIVITY COEFFICIENTS FOR THE NAOH-NAAL(OH)4-H2O SYSTEM AT 313.2 K - Zhou J.; Chen Q.Y.; Li J.; Yin Z.L.; Zhang P.M.; Zhou X. (My University, 2003)
By using a specially designed and constructed isopiestic apparatus, we measured the osmotic coefficients at 313.2 K for the NaOH-NaAl(OH)4-H2O system with the total alkali molality, mNaOHT (mNaOH + mNaAl[OH]4), from 0.05 mol/kg H2O to 12 mol/kg H2O and αK (mNaOHT/mNaAl(OH)4) from 1.64 to 5.53. The mean standard deviation of the measurements is 0.0038. Several sets of the Pitzer model parameters for NaOH-NaAl(OH)4-H2O system were then obtained by regressing the measured osmotic coefficients with the Pitzer model and the Pitzer model parameters for NaOH(aq). One set of the results is as follows: β(0)NaOH: 0.08669, β(1)NaOH: 0.31446, β(2)NaOH: −0.00007367, CΦNaOH: 0.003180, β(0)NaAl(OH)4: 0.03507, β(1)NaAl(OH)4: 0.02401, CΦNaAl(OH)4: −0.001066, θOH−Al(OH)4−: 0.08177, ΨNa+OH−Al(OH)4−: −0.01162. The mean standard difference between the calculated and the measured osmotic coefficients is 0.0088. With the obtained Pitzer model parameters, we calculated the values of K = (γNaAl(OH)4,cal2 · mAl(OH)4−,exp)/(γNaOH,cal2 · mOH−,exp) for the gibbsite solubility. The results show that the obtained Pitzer model parameters are reliable, and the relative error of the calculated activity coefficients should be < 2.1%. We also compared the calculated gibbsite solubility data among several activity coefficients models over a range of mNaOHT at various temperatures. The comparison indicates that our activity coefficients model may be approximately applied in the ranges of temperature from 298.2 to 323.2 K and mNaOHT from 0 to 8 mol/kg H2O. We also calculated the stoichiometric activity coefficients of NaOH and NaAl(OH)4 and the activity of H2O for the NaOH-NaAl(OH)4-H2O system, and these calculations establish their variations with mNaOHT and αK. These variations imply that the strengths of the repulsive interactions among various anions are in the following sequence: Al(OH)4−-Al(OH)4− < Al(OH)4−-OH− < OH−-OH−, and the attractive interaction between Al(OH)4− and H2O is weaker than that between OH− and H2O.